A Nitrate-Blind P. putida Strain Boosts PHA Production in a Synthetic Mixed Culture - Hobmeier, Karina; Löwe, Hannes; Liefeldt, Stephan; Kremling, Andreas; Pflüger-Grau, Katharina (Frontiers in Bioengineering and Biotechnology, 2020)
One of the major challenges for the present and future generations is to find suitable substitutes for the fossil resources we rely on today. In this context, cyanobacterial carbohydrates have been discussed as an emerging renewable feedstock in industrial biotechnology for the production of fuels and chemicals. Based on this, we recently presented a synthetic bacterial co-culture for the carbon-neutral production of medium-chain-length polyhydroxyalkanoates (PHAs) from CO2. This co-cultivation system is composed of two partner strains: Synechococcus elongatus cscB, which fixes CO2, converts it to sucrose, and exports it into the culture supernatant, and a Pseudomonas putida strain, which metabolizes this sugar and accumulates PHAs in the cytoplasm. However, these biopolymers are preferably accumulated under conditions of nitrogen limitation, a situation difficult to achieve in a co-culture as the other partner, at best, should not perceive any limitation. In this article, we will present an approach to overcome this dilemma by uncoupling the PHA production from the presence of nitrate in the medium. This is achieved by the construction of a P. putida strain that is no longer able to grow with nitrate as nitrogen source -is thus nitrate blind, and able to grow with sucrose as carbon source. The deletion of the nasT gene encoding the response regulator of the NasS/NasT two-component system resulted in such a strain that has lost the ability use nitrate, but growth with ammonium was not affected. Subsequently, the nasT deletion was implemented in P. putida cscRABY, an efficient sucrose consuming strain. This genetic engineering approach introduced an artificial unilateral nitrogen limitation in the co-cultivation process, and the amount of PHA produced from light and CO2 was considerably increased. This nitrate blind strain, P. putida ΔnasT attTn7::cscRABY, is not only a valuable partner in the co-cultivation but additionally opens up the use of other nitrate containing substrates for medium-chain-length PHA production, like for example waste-water.